2020
DOI: 10.4491/eer.2018.332
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol degradation and kinetics by advanced oxidation processes (AOPs): Electro-peroxone, ozonation, goethite catalyzed electro-fenton and electro-oxidation

Abstract: The advanced oxidation of paracetamol (PCT), frequently used analgesic, promoted by electro-oxidation (EOX), goethite catalyzed electro-Fenton (GEF) with goethite, ozonation and electro-peroxone (E-peroxone) was investigated. The degradation efficiency of the processes was evaluated considering the decay of PCT versus time. All the processes showed pseudo-first order character for PCT degradation. kobs values, at optimum conditions for an individual process, were defined as 0.0022, 0.0029, 0.0870 and 0.1662 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 43 publications
1
5
1
Order By: Relevance
“…A previous study reported a pseudo-first order kinetic rate constant of 0.087 min −1 by ozonation, for an initial PCT concentration of 100 mg L −1 , at pH 6.8 and an ozone flow rate of 5 L min −1 [31]. This constant is about five-fold lower than that of the present study (see Table 3), which is likely related to the higher initial concentration used in referred study.…”
Section: Degradation Of Individual Ppcpscontrasting
confidence: 79%
“…A previous study reported a pseudo-first order kinetic rate constant of 0.087 min −1 by ozonation, for an initial PCT concentration of 100 mg L −1 , at pH 6.8 and an ozone flow rate of 5 L min −1 [31]. This constant is about five-fold lower than that of the present study (see Table 3), which is likely related to the higher initial concentration used in referred study.…”
Section: Degradation Of Individual Ppcpscontrasting
confidence: 79%
“…This entails that a constant concentration of • OH always reacts with the contaminant (the reactant is considered in excess) on the anode surface during the full treatment time [ 95 , 96 ]. Based on the above considerations, Equation (15) can be rewritten as: where k ′ app = , and k ′ app is the pseudo-first-order kinetic constant [ 97 ].…”
Section: Mechanism Of Electrochemical Oxidation Of Organic Pollutantsmentioning
confidence: 99%
“…The degradation of azure B obeyed pseudo-first-order reaction kinetics ( k app of 0.37 min −1 after 500 min of treatment), suggesting that a constant amount of • OH reacts with the substrate at a given applied current density. Yet, Otzturk et al [ 97 ] examined the EO of paracetamol (PCT) using Pt anode. Even in this study, the PCT degradation rate was well described by pseudo-first-order kinetic.…”
Section: Mechanism Of Electrochemical Oxidation Of Organic Pollutantsmentioning
confidence: 99%
“…where k'app = ′ [ •] , k'app is the pseudo-first-order kinetic constant [94]. Most studies reported that the EO of organic pollutants exhibits pseudo-first-order kinetics, thus with the rate limited by mass transfer of the substrate from the bulk solution to the anode surface.…”
Section: Eo Degradation Kineticsmentioning
confidence: 99%
“…The degradation of azure B obeyed pseudo-first-order reaction kinetics (kapp of 0.37 min -1 after 500 min of treatment), suggesting that a constant amount of • OH reacts with the substrate at a given applied current density. Yet, Otzturk et al [94] examined the EO of paracetamol (PCT) using Pt anode. Even in this study, the PCT degradation rate was well-described by pseudo-first-order kinetic.…”
Section: Eo Degradation Kineticsmentioning
confidence: 99%